What should graduates have to sell themselves? / Nor Haniza Hasan and Tuan Sarifah Aini Syed Ahmad - Hasan, Nor Haniza; Syed Ahmad, Tuan Sarifah Aini (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
Graduates are like diamonds. The quality of diamonds is determined by 4Cs which are clarity, colour, cut and carat weight. As for graduates, their quality also depends on 4Cs which are referred to four skills namely communication, collaboration, creative thinking, and critical thinking. This article thus illustrates how crucial these 4Cs are to make them more outstanding, "saleable" in the job market and can perform their jobs effectively. To begin with, communication at the workplace is not only being able to be proficient in a language, especially English. Graduates also need to be sensitive to cultures. Moreover, with the advancement of technology especially in the Internet of Things (IoT), the world becomes borderless. Thus, working space can occur virtually involving people from anywhere in the world as geographical location is not a restriction anymore. Communication at the workplace just occurs online involving employees from various countries which have different cultures. This commonly happens in multinational companies which usually set a team for performing tasks to solve global challenges faced by the company. Therefore, it is insufficient for 21st century graduates to be only proficient at languages, but they must also be aware of different cultures in order to be effective and efficient in a geographical borderless workplace.